Identification and Evaluation of the Components of Regulatory Effectiveness in the Iranian Insurance Industry - Yousefnejad, Mahsa; Sarraf, Fatemeh; Beikzadeh Abbasi, Farzaneh; Taghi Nataj Malekshah, Gholam Hasan (Business, Marketing, and Finance Open, 2027)
The present study was conducted with the aim of identifying and evaluating the components of regulatory effectiveness in the Iranian insurance industry. In terms of purpose, the study was applied research; in terms of data type, it employed a sequential mixed-methods design with an exploratory approach; and in terms of nature, it consisted of a qualitative phase based on meta-synthesis/Delphi methodology and a quantitative phase based on descriptive-analytical (survey/correlational) methods. The qualitative population in the first stage included all relevant theoretical foundations and previous studies retrieved from domestic and international databases. Among these, 18 scientific publications were selected using a systematic exclusion technique and purposive non-probability sampling. In the second stage, the qualitative population consisted of theoretical and practical experts, from whom 19 participants were selected through the minimum sample size approach in the Delphi method and purposive non-probability sampling. The quantitative population comprised senior managers of the Financial Deputy Division of the Iranian Insurance Company. A total of 219 managers were selected as the sample using proportionate stratified random sampling and based on the minimum sample size requirement for confirmatory factor analysis. Data collection in the qualitative phase involved a systematic literature review during the meta-synthesis stage and a worksheet (semi-open-ended questionnaire) during the Delphi stage. In the quantitative phase, a researcher-developed questionnaire was used to assess the validity of the model from the perspectives of both the qualitative participants and the quantitative respondents. The validity and reliability of the instrument were examined and confirmed in both the qualitative and quantitative phases. Data analysis in the qualitative phase was conducted through thematic analysis following the approach of Braun and Clarke (2020) using MAXQDA 2018 software. In the quantitative phase, descriptive statistics (demographic characteristics and variables) and inferential statistical analyses (confirmatory factor analysis and one-sample t-test) were performed using SPSS Version 27 and SmartPLS Version 3. The findings indicated that the construct of regulatory effectiveness in the Iranian insurance industry consists of three dimensions: regulatory transparency (6 items), compliance (9 items), and risk prevention (9 items). Finally, based on the identified factors, the research model was developed. The results demonstrated both the internal and external validity of the model based on the evaluations of the qualitative participants and the quantitative respondents.